Cover Feature: Interconnected Two‐dimensional Arrays of Niobium Nitride Nanocrystals as Stable Lithium Host (Batteries & Supercaps 1/2021). Issue 1 (10th December 2020) - Xiao, Xu; Yao, Wei; Tang, Jun; Liu, Chuanfang; Lian, Ruqian; Urbankowski, Patrick; Anayee, Mark; He, Shijie; Li, Jianmin; Wang, Hao; Gao, Yu; Wei, Yingjin; et al.
Abstract : The Cover Feature illustrates 2D arrays of NbN nanocrystals, which are used as stable Li host. Coupled with lithium nickel–manganese–cobalt oxide, a long‐term cycling full Li‐metal battery is realized under practical condition. More information can be found in the Communication by Y. Gogotsi and co‐workers .